FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA KANTOR KECAMATAN MANDE KABUPATEN CIANJUR - Syuryani Hasan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Job career is a process undertaken by every individual by way of collecting information about values, preferences, skills, strengths, and weaknesses. It needs identification of career goal and the implementation of career strategies. Careermanagement and development system can improve work motivation and commitment as there are positive correlations among career management, performance, attitudes, and participation. Support from organization leaders for the employees to actively participate in pursuing their own careers is crucial, without which employees find difficulties to carry out selfdevelopment. This shows career management highly influence employees' development, especially thorugh career studies, career goal, and implementation of career strategies conducted by individuals so that they are motivated to develop themselves, which eventually shapes their performance. Training, motivation, and career path contribute 52.5% to the employees' performance at Cimande Subdistrict Office, and the rest 47.5% is influenced by other factors.